2005
DOI: 10.1002/ijc.20802
|View full text |Cite
|
Sign up to set email alerts
|

Serial in vivo loss and in vitro gain of Fas expression and function in human cancerous pancreatic duct cells

Abstract: Recent studies have shown the involvement of the Fas system (Fas receptor and its ligand FasL) in cancerous processes. The absence or downregulation of Fas, reported in the majority of human tumors, conflicts with its presence in cancerous cells from the same tumors but maintained in vitro. Recently, the eventual role of environmental factors in the loss of Fas expression, or in the in vivo selection of a Fas-negative cell population has been suggested. We determined the Fas expression and function in the Capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
0
9
0
1
Order By: Relevance
“…FAS is a member of the TNF-receptor superfamily and contains a death domain. FAS has been shown to play a central role in the physiological regulation of programmed cell death, and has been implicated in the pathogenesis of various malignancies and diseases of the immune system (Hiraide et al 2005;Radfar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…FAS is a member of the TNF-receptor superfamily and contains a death domain. FAS has been shown to play a central role in the physiological regulation of programmed cell death, and has been implicated in the pathogenesis of various malignancies and diseases of the immune system (Hiraide et al 2005;Radfar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since recent studies have suggested that resistance to apoptosis is associated with the loss of Fas function in several malignancies [24][25][26][27], up-regulating Fas expression on MGC-803 cells by YWKLF rabbit serum may increase cell sensitivity to FasL killing.…”
Section: Fas/fasl Expression In Mgc-803 Cellsmentioning
confidence: 99%
“…Fas expression and the sensitivity to Fas-mediated apoptosis in human pancreatic cell lines maintained in vitro, however, conflicts with recent findings indicating the mentioned absence or downregulation of Fas expression and function in most human solid tumors, including pancreatic malignancies [21]. There is also reduction in the Fas mRNAs expression in these tumor cells [21]. Thus, they are resistant to Fas-mediated apoptosis, due to absence or weakness in membrane-Fas expression.…”
Section: Fas-fasl Complexmentioning
confidence: 65%
“…These Fas positive cells are sensitive to Fas-mediated apoptosis when maintained in monolayer cultures, in vitro [21]. Fas expression and the sensitivity to Fas-mediated apoptosis in human pancreatic cell lines maintained in vitro, however, conflicts with recent findings indicating the mentioned absence or downregulation of Fas expression and function in most human solid tumors, including pancreatic malignancies [21]. Specifically, when these cells are xenografted into nude mice, the expression of Fas is lost in the majority of the tumors.…”
Section: Fas-fasl Complexmentioning
confidence: 99%